2020
DOI: 10.1504/ijkl.2020.10033151
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of stress factors among post-graduate students / a case of Aligarh Muslim University, Aligarh (India)

Abstract: We study the Kramers-Wannier duality for the transverse-field Ising lattice on a ring. A careful consideration of the ring boundary conditions shows that the duality has to be implemented with a proper treatment of different charge sectors of both the twisted and untwisted Ising and the dual-Ising Hilbert spaces. We construct a superoperator that explicitly maps the Ising operators to the dual-Ising operators. The superoperator naturally acts on the tensor product of the Ising and the dual-Ising Hilbert space.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…These range from his father's initial residence and service as a military judge in Lahore under the Ghaznavids to his presence there during its conquest by the Ghuris in 1186. 12 Minhaj's approach as a historian was determined by his family background and the circumstances of his life. Many political, social and religious factors had gone into the making of his personality and had conditioned his attitude towards religious and political problems of the period.…”
Section: Biographical Historymentioning
confidence: 99%
See 1 more Smart Citation
“…These range from his father's initial residence and service as a military judge in Lahore under the Ghaznavids to his presence there during its conquest by the Ghuris in 1186. 12 Minhaj's approach as a historian was determined by his family background and the circumstances of his life. Many political, social and religious factors had gone into the making of his personality and had conditioned his attitude towards religious and political problems of the period.…”
Section: Biographical Historymentioning
confidence: 99%
“…Tabaqat-i-Nasiri, Vol 1, pp. 277-288 12 Jawan Shir Rasik, Many Lives, pp. 120-22 13 Khalique Ahmed Nizami, On History and Historians of Medieval India, Munshiram Manohar Lal Publishers Pvt.…”
Section: Biographical Historymentioning
confidence: 99%
“…Remarks. The generic characteristics were summarized by Khan (2000), but the description about wing venation was incomplete. In addition, the lengths of the maxillary palpus and labial palpus were identical in Khan's description, while we found that both have their ends at the same height but they are of different lengths.…”
Section: Bradina Lederer 1863mentioning
confidence: 99%
“…Additionally, they lacked mechanical strength, structural stability, and durability. Organic membranes have lower permeability, selectivity, and fouling protection [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these disadvantages, enormous works have been done on inorganic components used in the creation of advanced membrane. Inorganic membranes have the advantage of high chemical thermal & mechanical strength & have high resistance to pH [13,14,15,16,17,18]. They show great kinetics of sorption and produce a lot of ionizing radiation [19,20,21].…”
Section: Introductionmentioning
confidence: 99%